Advanced hydraulic engineering : applications and optimization - Haddout, Soufiane; Priya, K. L. (CRC Press, 2025)
Advanced Hydraulic Engineering: Applications and Optimization is a comprehensive resource that delves into the advanced principles, methodologies, and real-world applications of hydraulic engineering. It discusses emerging trends and challenges in hydraulic engineering from the integration of artificial intelligence and machine learning to the pursuit of sustainable practices.Focusing on practical applications, the book provides case studies in water management, environmental protection, marine hydraulic propulsion, and industrial applications. It explains how the integration of Internet of Things (IoT) technology allows for remote monitoring and control of hydraulic equipment, facilitating proactive maintenance and troubleshooting to prevent costly downtime and equipment failures. Advances in sensor technology, data analytics, and automation and their role in revolutionizing the field of hydraulics are also addressed.This book is intended for practicing engineers, industry professionals, and academics involved in the design, maintenance, and applications of hydraulic systems.
Keywords: Hydraulic engineering.; Hydraulics.; Internet of things.; elektronické knihy; electronic books